A Study of Consumer Behaviour Towards Fast Moving Consumer Goods - Mahadira, Fabila; Purwanegara, Mustika Sufiati (Journal of Business and Management, 2014)
Abstract â€ The research was constructed to study the consumer behavior towards fast-moving consumer goods through interpreting how brand awareness and consumption correlated, and examining the customer satisfaction. This theme arise because nowadays every company knew the key to the issue of war between products is to get the answer on how to win the war and be on top of the competition, and the answer is simply to make customers become loyal to the product. Therefore a study on how to win the customer heart and make them loyal should be conducted as well as analyzing the main factor that influences the result of consumer loyalty, which is consumer behavior, and brand consumption and consumer satisfaction are two of the important factor that included in consumer behavior. The research is conducted between May 2013 to October 2013 using quantitative questionnaires which spread to specific target of sampling that consist of both male and female adult with 50:50 proportion, those between 20 to 40 years old and above, and have a source of income. The data is then examined and evaluated using Microsoft Officeâ€™s Excel and IBMâ€™s SPSS to create a list of products and calculate mean score. The findings presents that most of the products and brands have successfully proved that their brand is not just a mere sensation to attract awareness of consumer, but a real deal product and brand that satisfied their consumer.Â Keywords: Brand Awareness, Brand Consumption, Satisfaction, Consumer Behavior, Fast-Moving Consumer Goods